The Tendency Of Teachers’ Feedback On Students’ English Writing Work - Mariam, Cucu; Hidayati, Poppy Sofia (UNIVERSITAS PAKUAN, 2023)
The objectives of this study were to find out the kinds and categories of teachers’ written feedback on the students’ writing work in high schools in Bogor. This research used descriptive qualitative method and the data were collected through observation, documentation and interview. The samples consisted of five English Teachers from several high schools in Bogor and 40 students’ English writing work. The findings found that 38% feedback is belong to direct written feedback by giving the response using written comments and the highest categories is holistic remarks, it is 34%. In conclusion, the teachers’ feedback in High Schools in Bogor tends to use direct written feedback by responding using the comments and using holistic categories. In other words, the tendency of teachers’ feedback on the students’ English writing work is using direct written by responding and holistic remark